ANALISIS TINGKAT RISIKO KELUHAN OTOT DENGAN METODE HARM (HAND AND ARM RISK METHOD) PADA PENGEMUDI BUS DI PT SAHABAT PRIMA ABADI - Tsaniya Barrani Faza (2023)
The 14 tour bus drivers at PT Sahabat Prima Abadi are on duty for an average of 9-10 hours per day with an indeterminate rest duration. This causes muscle complaints felt by the driver. The purpose of this study is to determine the risk level of muscle complaints in bus drivers using the HARM (Hand And Arm Risk Method), see the relationship between individual factors (body mass index, age, smoking habits and physical fitness) with musculoskeletal disorders and provide appropriate improvement recommendations. Assessment of the risk level of muscle complaints with the HARM method by observing videos of work activities. The relationship between individual factors and muscle complaints was analyzed using the spearman rho test. The HARM method assessment score was 73,5, the risk level of muscle complaints in the neck, arms and shoulders indicates a high potential risk and requires immediate corrective action. The spearman test shows a significant relationship and strong correlation between individual factors, namely age, smoking habits and physical fitness with muscle complaints. While the individual factor of body size has a weak and insignificant correlation. Recommendations for improvements that can be made by means of engineering and management engineering.